Examining 239+240Pu, 210Pb and historical events to determine carbon, nitrogen and phosphorus burial in mangrove sediments of Moreton Bay, Australia. (January 2016) - Sanders, Christian J.; Santos, Isaac R.; Maher, Damien T.; Breithaupt, Joshua L.; Smoak, Joseph M.; Ketterer, Michael; Call, Mitchell; Sanders, Luciana; Eyre, Bradley D.
Abstract: Two sediment cores were collected in a mangrove forest to construct geochronologies for the previous century using natural and anthropogenic radionuclide tracers. Both sediment cores were dated using 239+240 Pu global fallout signatures as well as 210 Pb, applying both the Constant Initial Concentration (CIC) and the Constant Rate of Supply (CRS) models. The 239+240 Pu and CIC model are interpreted as having comparable sediment accretion rates (SAR) below an apparent mixed region in the upper ∼5 to 10 cm. In contrast, the CRS dating method shows high sediment accretion rates in the uppermost intervals, which is substantially reduced over the lower intervals of the 100-year record. A local anthropogenic nutrient signal is reflected in the high total phosphorus (TP) concentration in younger sediments. The carbon/nitrogen molar ratios and δ 15 N values further support a local anthropogenic nutrient enrichment signal. The origin of these signals is likely the treated sewage discharge to Moreton Bay which began in the early 1970s. While the 239+240 Pu and CIC models can only produce rates averaged over the intervals of interest within the profile, the 210 Pb CRS model identifies elevated rates of sediment accretion, organic carbon (OC), nitrogen (N), and TP burial from 2000 to 2013. From 1920 to 2000, the three dating methods provide similar OC, N and TP burial rates, ∼150, 10 and 2 g m −2  year −1, respectively, which are comparable to global averages. Highlights: Lead-210 dating models indicate that the high phosphorous import to the tidal creek may increase mangrove OC burial. Combinations of sediment dating models ( 239+240 Pu, 210 Pb) are ideal in determining sediment accretion in marine sediments during the previous century. Decadal accretion rates, derived from the 239+240 Pu and 210 Pb dating models, are important to interpret anthropogenic effects on coastal systems. Carbon and nitrogen stable isotopes indicate diversified source of OM to impacted mangrove soils.